Price Gouging or Market Forces? Fairness Perceptions of Price Hikes during the Pandemic - Avichai Snir; Daniel Levy; Dudi Levy; Haipeng (Allan) Chen (Economics Bulletin, 2025)
We report the results of surveys we conducted in the US and Israel in 2020, a time when many prices increased following the spread of the COVID-19 pandemic. To assess respondents' fairness perceptions of price increases, we focus on goods whose prices have increased during the pandemic, including some essential goods. Consistent with the principle of dual entitlement, we find that respondents perceive price increases as fairer if they are due to cost shocks than if they are due to demand shocks. However, we also find large differences across the two populations, as well as across goods.
Additional information: The file contains the paper and the appendix
Keywords: E70; E31; D90; M31; 330; Dual Entitlement; Fairness Perceptions; Consumer Antagonism; COVID-19; Pandemic; Price Level; Price Adjustment; Price Increase; Price Hike; Price Rigidity; Price Stickiness; Rigid Prices; Sticky Prices; Consumer Behavior